Infection Augments Expression of Mechanosensing Piezo1 Channels in Amyloid Plaque-Reactive Astrocytes - Velasco-Estevez, María; Mampay, Myrthe; Boutin, Hervé; Chaney, Aisling; Warn, Peter; Sharp, Andrew; Burgess, Ellie; Moeendarbary, Emad; Dev, Kumlesh K.; Sheridan, Graham K. (Frontiers in Aging Neuroscience, 2018)
A defining pathophysiological hallmark of Alzheimer’s disease is the amyloid plaque; an extracellular deposit of aggregated fibrillar Aβ1-42 peptides. Amyloid plaques are hard, brittle structures scattered throughout the hippocampus and cerebral cortex and are thought to cause hyperphosphorylation of tau, neurofibrillary tangles, and progressive neurodegeneration. Reactive astrocytes and microglia envelop the exterior of amyloid plaques and infiltrate their inner core. Glia are highly mechanosensitive cells and can almost certainly sense the mismatch between the normally soft mechanical environment of the brain and very stiff amyloid plaques via mechanosensing ion channels. Piezo1, a non-selective cation channel, can translate extracellular mechanical forces to intracellular molecular signalling cascades through a process known as mechanotransduction. Here, we utilised an ageing transgenic rat model of Alzheimer’s disease (TgF344-AD) to study expression of mechanosensing Piezo1 ion channels in amyloid plaque-reactive astrocytes. We found that Piezo1 is upregulated with age in the hippocampus and cortex of 18-month old wild-type rats. However, more striking increases in Piezo1 were measured in the hippocampus of TgF344-AD rats compared to age-matched wild-type controls. Interestingly, repeated urinary tract infections with E. coli bacteria, a common comorbidity in elderly people with dementia, caused further elevations in Piezo1 channel expression in the hippocampus and cortex of TgF344-AD rats. Taken together, we report that ageing and peripheral infection augment amyloid plaque-induced upregulation of mechanoresponsive ion channels, such as Piezo1, in astrocytes. Further research is required to investigate the role of astrocytic Piezo1 in the Alzheimer’s brain, whether modulating channel opening will protect or exacerbate the disease state, and most importantly, if Piezo1 could prove to be a novel drug target for age-related dementia.